Hubungan Pengetahuan Terhadap Sikap Remaja Desa Ujung Tanduk Kecamatan Laguboti Kabupaten Toba Tentang Swamedikasi Jerawat Tahun 2021 - Baharuddin J.E.A. Togatorop; Devi Yanthre Sari Manurung; Melva Epy Mardiana Manurung; Riris Sianipar (Program Studi S1 Farmasi, STIKES Senior, Medan, 2022)
Acne is one of the physical problems experienced during adolescence. The prevalence of acne sufferers in Indonesia ranges from 80-85% in adolescents with a peak incidence of 15-18 years of age. Acne often causes a lack of self-confidence of a teenager. A teenager with acne will try to treat it and treatment in general will be done with self-medication. A person's knowledge and attitude will affect the individual's way of behaving, including in carrying out treatment by means of self-medication. This research was conducted on teenagers in Ujung Tanduk Village, Laguboti District, Toba Regency where there were 60 populations and samples were taken as many as 45 respondents, which were collected in WhatsApp groups. Based on the research that has been carried out, 64.4% of respondents have good knowledge and the remaining 35.6% are knowledgeable enough and there are 48.9% of respondents who have good attitudes, 33.3% are moderate and 17.8% have poor attitudes, and found a relationship between knowledge and good attitudes. evidenced by the results of statistical tests (Chi Square test) where the p value <0.05.